Basic Motor Competencies of 6- to 8-Year-Old Primary School Children in 10 European Countries: A Cross-Sectional Study on Associations With Age, Sex, Body Mass Index, and Physical Activity - Wälti, Marina; Sallen, Jeffrey; Adamakis, Manolis; Ennigkeit, Fabienne; Gerlach, Erin; Heim, Christopher; Jidovtseff, Boris; Kossyva, Irene; Labudová, Jana; Masaryková, Dana; Mombarg, Remo; De Sousa Morgado, Liliane; et al. (Frontiers in Psychology, 2022)
Basic motor competencies (BMC) are a prerequisite for children to be physically active, participate in sports and thus develop a healthy, active lifestyle. The present study provides a broad screening of BMC and associations with age, sex, body mass index (BMI) and extracurricular physical activity (PA) in 10 different European countries. The different country and regional contexts within Europe will offer a novel view on already established BMC associations. The cross-sectional study was conducted in 11 regions in 10 European countries in 2018. The motor competence areas, object movement (OM) and self-movement (SM), were assessed using the MOBAK-1-2 test instrument in 3758 first and second graders (age: M = 6.86 ± 0.60 years; 50% girls) during Physical Education classes. Children were questioned about their extracurricular PA and age. Their body weight and height were measured in order to calculate BMI. Statistical analyses included variances and correlations. The results showed significant differences in BMC levels between countries (OM: F = 18.74, p < 0.001, η2 = 0.048; SM: F = 73.10, p < 0.001, η2 = 0.163) whereas associations between BMC and correlates were similar. Boys performed significantly better in OM while girls performed better in SM. Age was consistently positively related to OM and SM with older children reaching higher levels of BMC than younger ones. While participation rates for extracurricular PA differed widely, participation in ball sports was correlated with OM and SM. Participation in individual sports showed a significant association with SM. In summary, BMC levels of children seem to depend on where they live and are strongly related to their participation in extracurricular PA. Therefore, education and health policies, in order to enhance motor competence development and PA participation, are recommended. Further research on country-specific Physical Education frameworks and their influence on BMC will provide more insights into structural factors and cultural characteristics of BMC development. On a school level, support tools and educational materials for teachers about BMC may enable children to achieve a basic level of motor competencies through Physical Education, contributing to lifelong participation in PA.